Analysis of paternal smoke exposure and childhood obesity - Göney, Gülşen; Halısdemır, Nurhan (My University, 2021)
Studies reported that parental smoking exposure may be a risk factor for childhood obesity. Present study analyzed that relationship between paternal smoking exposure and children's body mass index. We aim to evaluate that possible obesogenic effects of paternal smoke exposure. This is a cross sectional analysis of a survey from April to December 2020. A survey was performed to fathers aim to learn nourishment and smoking status and children to learn nourishment and lifestyle. Participants were classified according to body mass index results. The study group was formed of 272 individual (136 fathers, Mage=41.03±8.40 years and 136 children, Mage=4.19±1.25 years). In present research, 10.3% of children were overweight, and 2.9% obese. Also, 52.9% of children had smoking exposure and 10.3% were overweight whereas 2.9% of children were obese. Our results put forward that the relation between paternal smoking and children's body mass index was nonsignificant (p>0.05). This is the seminal study in Turkey analysis that obesogenic effect of paternal smoke exposure, In the future, more studies need to evaluate the relation of paternal smoking exposure and child obesity
Keywords: Beslenme ve Diyetetik; Pediatri